test_gosper.py 7.8 KB

123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133134135136137138139140141142143144145146147148149150151152153154155156157158159160161162163164165166167168169170171172173174175176177178179180181182183184185186187188189190191192193194195196197198199200201202203204
  1. """Tests for Gosper's algorithm for hypergeometric summation. """
  2. from sympy.core.numbers import (Rational, pi)
  3. from sympy.core.singleton import S
  4. from sympy.core.symbol import Symbol
  5. from sympy.functions.combinatorial.factorials import (binomial, factorial)
  6. from sympy.functions.elementary.exponential import (exp, log)
  7. from sympy.functions.elementary.miscellaneous import sqrt
  8. from sympy.functions.special.gamma_functions import gamma
  9. from sympy.polys.polytools import Poly
  10. from sympy.simplify.simplify import simplify
  11. from sympy.concrete.gosper import gosper_normal, gosper_sum, gosper_term
  12. from sympy.abc import a, b, j, k, m, n, r, x
  13. def test_gosper_normal():
  14. eq = 4*n + 5, 2*(4*n + 1)*(2*n + 3), n
  15. assert gosper_normal(*eq) == \
  16. (Poly(Rational(1, 4), n), Poly(n + Rational(3, 2)), Poly(n + Rational(1, 4)))
  17. assert gosper_normal(*eq, polys=False) == \
  18. (Rational(1, 4), n + Rational(3, 2), n + Rational(1, 4))
  19. def test_gosper_term():
  20. assert gosper_term((4*k + 1)*factorial(
  21. k)/factorial(2*k + 1), k) == (-k - S.Half)/(k + Rational(1, 4))
  22. def test_gosper_sum():
  23. assert gosper_sum(1, (k, 0, n)) == 1 + n
  24. assert gosper_sum(k, (k, 0, n)) == n*(1 + n)/2
  25. assert gosper_sum(k**2, (k, 0, n)) == n*(1 + n)*(1 + 2*n)/6
  26. assert gosper_sum(k**3, (k, 0, n)) == n**2*(1 + n)**2/4
  27. assert gosper_sum(2**k, (k, 0, n)) == 2*2**n - 1
  28. assert gosper_sum(factorial(k), (k, 0, n)) is None
  29. assert gosper_sum(binomial(n, k), (k, 0, n)) is None
  30. assert gosper_sum(factorial(k)/k**2, (k, 0, n)) is None
  31. assert gosper_sum((k - 3)*factorial(k), (k, 0, n)) is None
  32. assert gosper_sum(k*factorial(k), k) == factorial(k)
  33. assert gosper_sum(
  34. k*factorial(k), (k, 0, n)) == n*factorial(n) + factorial(n) - 1
  35. assert gosper_sum((-1)**k*binomial(n, k), (k, 0, n)) == 0
  36. assert gosper_sum((
  37. -1)**k*binomial(n, k), (k, 0, m)) == -(-1)**m*(m - n)*binomial(n, m)/n
  38. assert gosper_sum((4*k + 1)*factorial(k)/factorial(2*k + 1), (k, 0, n)) == \
  39. (2*factorial(2*n + 1) - factorial(n))/factorial(2*n + 1)
  40. # issue 6033:
  41. assert gosper_sum(
  42. n*(n + a + b)*a**n*b**n/(factorial(n + a)*factorial(n + b)), \
  43. (n, 0, m)).simplify() == -exp(m*log(a) + m*log(b))*gamma(a + 1) \
  44. *gamma(b + 1)/(gamma(a)*gamma(b)*gamma(a + m + 1)*gamma(b + m + 1)) \
  45. + 1/(gamma(a)*gamma(b))
  46. def test_gosper_sum_indefinite():
  47. assert gosper_sum(k, k) == k*(k - 1)/2
  48. assert gosper_sum(k**2, k) == k*(k - 1)*(2*k - 1)/6
  49. assert gosper_sum(1/(k*(k + 1)), k) == -1/k
  50. assert gosper_sum(-(27*k**4 + 158*k**3 + 430*k**2 + 678*k + 445)*gamma(2*k
  51. + 4)/(3*(3*k + 7)*gamma(3*k + 6)), k) == \
  52. (3*k + 5)*(k**2 + 2*k + 5)*gamma(2*k + 4)/gamma(3*k + 6)
  53. def test_gosper_sum_parametric():
  54. assert gosper_sum(binomial(S.Half, m - j + 1)*binomial(S.Half, m + j), (j, 1, n)) == \
  55. n*(1 + m - n)*(-1 + 2*m + 2*n)*binomial(S.Half, 1 + m - n)* \
  56. binomial(S.Half, m + n)/(m*(1 + 2*m))
  57. def test_gosper_sum_algebraic():
  58. assert gosper_sum(
  59. n**2 + sqrt(2), (n, 0, m)) == (m + 1)*(2*m**2 + m + 6*sqrt(2))/6
  60. def test_gosper_sum_iterated():
  61. f1 = binomial(2*k, k)/4**k
  62. f2 = (1 + 2*n)*binomial(2*n, n)/4**n
  63. f3 = (1 + 2*n)*(3 + 2*n)*binomial(2*n, n)/(3*4**n)
  64. f4 = (1 + 2*n)*(3 + 2*n)*(5 + 2*n)*binomial(2*n, n)/(15*4**n)
  65. f5 = (1 + 2*n)*(3 + 2*n)*(5 + 2*n)*(7 + 2*n)*binomial(2*n, n)/(105*4**n)
  66. assert gosper_sum(f1, (k, 0, n)) == f2
  67. assert gosper_sum(f2, (n, 0, n)) == f3
  68. assert gosper_sum(f3, (n, 0, n)) == f4
  69. assert gosper_sum(f4, (n, 0, n)) == f5
  70. # the AeqB tests test expressions given in
  71. # www.math.upenn.edu/~wilf/AeqB.pdf
  72. def test_gosper_sum_AeqB_part1():
  73. f1a = n**4
  74. f1b = n**3*2**n
  75. f1c = 1/(n**2 + sqrt(5)*n - 1)
  76. f1d = n**4*4**n/binomial(2*n, n)
  77. f1e = factorial(3*n)/(factorial(n)*factorial(n + 1)*factorial(n + 2)*27**n)
  78. f1f = binomial(2*n, n)**2/((n + 1)*4**(2*n))
  79. f1g = (4*n - 1)*binomial(2*n, n)**2/((2*n - 1)**2*4**(2*n))
  80. f1h = n*factorial(n - S.Half)**2/factorial(n + 1)**2
  81. g1a = m*(m + 1)*(2*m + 1)*(3*m**2 + 3*m - 1)/30
  82. g1b = 26 + 2**(m + 1)*(m**3 - 3*m**2 + 9*m - 13)
  83. g1c = (m + 1)*(m*(m**2 - 7*m + 3)*sqrt(5) - (
  84. 3*m**3 - 7*m**2 + 19*m - 6))/(2*m**3*sqrt(5) + m**4 + 5*m**2 - 1)/6
  85. g1d = Rational(-2, 231) + 2*4**m*(m + 1)*(63*m**4 + 112*m**3 + 18*m**2 -
  86. 22*m + 3)/(693*binomial(2*m, m))
  87. g1e = Rational(-9, 2) + (81*m**2 + 261*m + 200)*factorial(
  88. 3*m + 2)/(40*27**m*factorial(m)*factorial(m + 1)*factorial(m + 2))
  89. g1f = (2*m + 1)**2*binomial(2*m, m)**2/(4**(2*m)*(m + 1))
  90. g1g = -binomial(2*m, m)**2/4**(2*m)
  91. g1h = 4*pi -(2*m + 1)**2*(3*m + 4)*factorial(m - S.Half)**2/factorial(m + 1)**2
  92. g = gosper_sum(f1a, (n, 0, m))
  93. assert g is not None and simplify(g - g1a) == 0
  94. g = gosper_sum(f1b, (n, 0, m))
  95. assert g is not None and simplify(g - g1b) == 0
  96. g = gosper_sum(f1c, (n, 0, m))
  97. assert g is not None and simplify(g - g1c) == 0
  98. g = gosper_sum(f1d, (n, 0, m))
  99. assert g is not None and simplify(g - g1d) == 0
  100. g = gosper_sum(f1e, (n, 0, m))
  101. assert g is not None and simplify(g - g1e) == 0
  102. g = gosper_sum(f1f, (n, 0, m))
  103. assert g is not None and simplify(g - g1f) == 0
  104. g = gosper_sum(f1g, (n, 0, m))
  105. assert g is not None and simplify(g - g1g) == 0
  106. g = gosper_sum(f1h, (n, 0, m))
  107. # need to call rewrite(gamma) here because we have terms involving
  108. # factorial(1/2)
  109. assert g is not None and simplify(g - g1h).rewrite(gamma) == 0
  110. def test_gosper_sum_AeqB_part2():
  111. f2a = n**2*a**n
  112. f2b = (n - r/2)*binomial(r, n)
  113. f2c = factorial(n - 1)**2/(factorial(n - x)*factorial(n + x))
  114. g2a = -a*(a + 1)/(a - 1)**3 + a**(
  115. m + 1)*(a**2*m**2 - 2*a*m**2 + m**2 - 2*a*m + 2*m + a + 1)/(a - 1)**3
  116. g2b = (m - r)*binomial(r, m)/2
  117. ff = factorial(1 - x)*factorial(1 + x)
  118. g2c = 1/ff*(
  119. 1 - 1/x**2) + factorial(m)**2/(x**2*factorial(m - x)*factorial(m + x))
  120. g = gosper_sum(f2a, (n, 0, m))
  121. assert g is not None and simplify(g - g2a) == 0
  122. g = gosper_sum(f2b, (n, 0, m))
  123. assert g is not None and simplify(g - g2b) == 0
  124. g = gosper_sum(f2c, (n, 1, m))
  125. assert g is not None and simplify(g - g2c) == 0
  126. def test_gosper_nan():
  127. a = Symbol('a', positive=True)
  128. b = Symbol('b', positive=True)
  129. n = Symbol('n', integer=True)
  130. m = Symbol('m', integer=True)
  131. f2d = n*(n + a + b)*a**n*b**n/(factorial(n + a)*factorial(n + b))
  132. g2d = 1/(factorial(a - 1)*factorial(
  133. b - 1)) - a**(m + 1)*b**(m + 1)/(factorial(a + m)*factorial(b + m))
  134. g = gosper_sum(f2d, (n, 0, m))
  135. assert simplify(g - g2d) == 0
  136. def test_gosper_sum_AeqB_part3():
  137. f3a = 1/n**4
  138. f3b = (6*n + 3)/(4*n**4 + 8*n**3 + 8*n**2 + 4*n + 3)
  139. f3c = 2**n*(n**2 - 2*n - 1)/(n**2*(n + 1)**2)
  140. f3d = n**2*4**n/((n + 1)*(n + 2))
  141. f3e = 2**n/(n + 1)
  142. f3f = 4*(n - 1)*(n**2 - 2*n - 1)/(n**2*(n + 1)**2*(n - 2)**2*(n - 3)**2)
  143. f3g = (n**4 - 14*n**2 - 24*n - 9)*2**n/(n**2*(n + 1)**2*(n + 2)**2*
  144. (n + 3)**2)
  145. # g3a -> no closed form
  146. g3b = m*(m + 2)/(2*m**2 + 4*m + 3)
  147. g3c = 2**m/m**2 - 2
  148. g3d = Rational(2, 3) + 4**(m + 1)*(m - 1)/(m + 2)/3
  149. # g3e -> no closed form
  150. g3f = -(Rational(-1, 16) + 1/((m - 2)**2*(m + 1)**2)) # the AeqB key is wrong
  151. g3g = Rational(-2, 9) + 2**(m + 1)/((m + 1)**2*(m + 3)**2)
  152. g = gosper_sum(f3a, (n, 1, m))
  153. assert g is None
  154. g = gosper_sum(f3b, (n, 1, m))
  155. assert g is not None and simplify(g - g3b) == 0
  156. g = gosper_sum(f3c, (n, 1, m - 1))
  157. assert g is not None and simplify(g - g3c) == 0
  158. g = gosper_sum(f3d, (n, 1, m))
  159. assert g is not None and simplify(g - g3d) == 0
  160. g = gosper_sum(f3e, (n, 0, m - 1))
  161. assert g is None
  162. g = gosper_sum(f3f, (n, 4, m))
  163. assert g is not None and simplify(g - g3f) == 0
  164. g = gosper_sum(f3g, (n, 1, m))
  165. assert g is not None and simplify(g - g3g) == 0